ENVIRONMENTALLY FRIENDLY BASED SMART VILLAGE PLANNING IN PERABAGA VILLAGE, PYRAMID DISTRICT, JAYAWIJAYA REGENCY, PAPUA MOUNTAIN PROVINCE, INDONESIA - soni, aprianto (USN Kolaka, 2023)
Natural damage creates an imbalance in the balance of the environment, many phenomena of environmental damage occur such as environmental damage such as environmental pollution, ecosystem damage and drought. This phenomenon still cannot be resolved and its impact affects human life. There is a need to create a sustainable environment in all levels of society, especially in rural areas. In the rural world, it appears that people lack awareness and environmentally friendly behavior. Therefore, the aim of this research is to describe the level of awareness and behavior of the community in the village. This research uses descriptive quantitative methods using interview techniques and data collection. The research results show that the level of public awareness is in the high category, but the level of environmentally friendly behavior of the public is in the medium category. These results show that society is already at the awareness stage where environmentally friendly behavior is important but its implementation is moderate, so that the awareness reflected in society is only theoretical and not in practice.